Ethnic Disparities and Inequalities in Dementia Care: An Extended Literature Review - Anita Okeoghene Ighomereho (BJPsych Open, 2025)
Aims: Dementia is a leading cause of disability and loss of independence among older people. There is growing concern about ethnic disparities and inequalities in dementia care. In the UK, Black and South Asian people have a higher risk of developing dementia compared with their White counterparts. Despite this, there is underrepresentation of minority ethnic groups in dementia services and they are more likely to have a delayed diagnosis or no diagnosis.